2021
DOI: 10.3390/ijerph18042126
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Metal-Induced Cellular Stress by α-Lipoic Acid and Dihydrolipoic Acid through Antioxidative Effects in PC12 Cells and Caco-2 Cells

Abstract: α-Lipoic acid (ALA) and its reduced form dihydrolipoic acid (DHLA) are endogenous dithiol compounds with significant antioxidant properties, both of which have the potential to detoxify cells. In this study, ALA (250 μM) and DHLA (50 μM) were applied to reduce metal (As, Cd, and Pb)-induced toxicity in PC12 and Caco-2 cells as simultaneous exposure. Both significantly decreased Cd (5 μM)-, As (5 μM)-, and Pb (5 μM)-induced cell death. Subsequently, both ALA and DHLA restored cell membrane integrity and intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…In this study, lead treatment could significantly decrease the level of GSH/GSSG, demonstrating its effect on the glutathione redox cycle. Lead treatment has been shown to decrease intracellular GSH levels, which is consistent with our findings ( 34 ). When preincubated with pea peptides and VC for lead treatment, PP3, PP4, PP6, and VC significantly increased GSH/GSSG and returned to normal levels compared to the lead group ( P < 0.05).…”
Section: Resultssupporting
confidence: 93%
“…In this study, lead treatment could significantly decrease the level of GSH/GSSG, demonstrating its effect on the glutathione redox cycle. Lead treatment has been shown to decrease intracellular GSH levels, which is consistent with our findings ( 34 ). When preincubated with pea peptides and VC for lead treatment, PP3, PP4, PP6, and VC significantly increased GSH/GSSG and returned to normal levels compared to the lead group ( P < 0.05).…”
Section: Resultssupporting
confidence: 93%
“…To explore in vitro effects of zinc acetate and rifaximin on enterocytes, we used the human colorectal adenocarcinoma line Caco-2. Caco-2 cells were obtained from Riken BRC Cell Bank (Ibaraki, Japan) and were cultured, as described previously[ 32 ]. The cells were cultured in Dulbecco’s modified Eagle’s medium supplemented with 100 U/mL of penicillin, 100 g/mL of streptomycin, 0.1-mM nonessential amino acids, 10-mM HEPES, and 10% fetal bovine serum at 37 °C in an environment with 5% carbon dioxide.…”
Section: Methodsmentioning
confidence: 99%
“…[110,121] Studies conducted in isolated rat liver mitochondria have shown the ameliorative effect of α-LA against the Asinduced oxidative stress. [122] Studies conducted in cell line models have revealed the protection of α-LA or dihydrolipoic acid against metal (arsenic, cadmium, lead) toxicity by reducing oxidative stress through the enhancement of an antioxidant defense mechanism. [123] 8.7 | Ascorbic acid and thiamine…”
Section: Melatoninmentioning
confidence: 99%